Analyzing the effect of time-varying factors for Thai rice export - Paravee Maneejuk (2018)
© 2016 by the Mathematical Association of Thailand. All rights reserved. This paper analyses the time-varying behaviors of some specific factors that affect the Thai rice export. We introduce the Markov switching regression with time-varying method as a contribution to a discussion on this issue. This model employs the Bayesian approach to do the parameter estimation of this model while Kalman filter is applied to predict the time-varying coefficient in each regime. The result shows that the proposed model is able to capture the real economic situation very well and can beat the conventional static Markov switching regression.